The politics of Covid-19 vaccine confidence. (August 2021) - Sabahelzain, Majdi M; Hartigan-Go, Kenneth; Larson, Heidi J
Highlights: The Covid-19 pandemic has seen political responses uniting and dividing publics. How governments handle the Covid-19 response impacts vaccine confidence. Political action or inaction in one country can impact others globally. Efforts to ensure equitable vaccine access must consider the reality of politics. Abstract : In the context of emerging COVID-19 virus variants, trends of vaccine nationalism, and multiple vaccine supply challenges, COVID-19 vaccine related uncertainties and challenges continue. Additionally, confidence in new COVID-19 vaccines is highly variable, with minority communities generally less trusting of not only the new vaccines, but also those who produce them and the governments buying and recommending them. How governments handle the COVID-19 response will be a key influencer of public confidence in and acceptance of COVID vaccination.